ESTERIFICATION OF FATTY ACID FROM PALM OIL WASTE (SLUDGE OIL) BY USING ALUM CATALYST - Thamrin Usman; Lucy Ariany; Winda Rahmalia; Romi Advant (Indonesian Journal of Chemistry, 2009)
Esterification of fatty acids from palm oil waste (sludge oil) as biodiesel liquid base has been done by using alum [Al2(SO4)3.14H2O] catalyst. Some reaction variables like reaction time, catalyst quantity, and molar ratio of sample-reactant was applied for optimal reaction. Yield of 94.66% was obtained at reaction condition 65 °C, 5 h, sample-reactant ratio 1:20, and catalyst quantity 3% (w/w). GC-MS analysis request showed that composition of methyl esters biodiesel are methyl caproic (0.67%), methyl lauric (0.21%), methyl miristic (1.96%), methyl palmitic (49.52%), methyl oleic (41.51%), and methyl stearic (6.13%). Physical properties of synthesized product (viscosity, refraction index and density) are similar with those of commercial product.